Effect of argon laser retinal photocoagulation on corneal parameters among proliferative diabetic retinopathy patients - Ghani, Siti Ilyana (2020)
Objectives Application of laser photocoagulation on the retina will start at a healthy and transparent central corneal surface so that laser waves cross the cornea to reach the retinal surface of area of interest to treat hypoxic and neovascularized area of the retina. The effect of laser photocoagulation to the cornea is mainly through thermal effect to the surrounding structures. The aim of this study was to document any effect of Argon laser pan retinal photocoagulation (PRP) on corneal parameters among proliferative diabetic retinopathy (PDR) patients. Methodology: This is a prospective cohort study involving newly diagnosed PDR patients who attended Ophthalmology Clinic Hospital Universiti Sains Malaysia from June 2017 till June 2019.The corneal structure was examined for central corneal thickness (CCT), endothelial cell density (CD) and coefficient of variation (CoV) of cell area. Images were obtained and analysed using specular microscope pre PRP and post completed PRP (at 1 week and 6 week post completed PRP). Laser PRP was performed using Zeiss Visulas 532 Nd Yag laser machine. Results: A total of 33 newly diagnosed PDR patients were included in this study. In this study, there was no significant reduction in the mean CD pre versus post argon laser PRP (p= 0.876). Neither CCT nor CoV showed statistical significant difference between pre and post completed PRP (p= 0.828 and p= 0.074 respectively). No correlation was found between amount of laser energy used and corneal cell parameters (p>0.05). Conclusion: In this study, we found that Argon laser PRP showed no significant effect on the corneal parameters (CCT, CD and CoV) among PDR patientsat 1 week and 6 weeks post completed PRP.Thus, further study of the issue is still required, as it remains to prove Argon laser PRP safety in patients with diabetic and other systemic co-morbididties.